Performance Comparison of WSN Topologies in IoT-Based Water Quality Monitoring Systems - Muhammad Imam Ghozali; Alif Catur Murti; Wibowo Harry Sugiharto; Klaus Roder (UIN Sumatera Utara, 2025)
This study, we quantify how WSN topology shapes QoS for IoT water-quality monitoring and derive deployment rules. Five topologies (Hybrid Star-Mesh, Cluster Tree, Full Mesh, Ring, ZigBee Star; 20 nodes) were simulated in NS-3 for 10 independent runs with random seeds. Our mathematical contribution is a compact QoS model set-latency LLL, packet-loss PlossP_loss Ploss, bandwidth usage UBU_BUB, and throughput TTT-used to compare topologies and compute relative/absolute improvements. Statistics report mean±SD with 95% confidence intervals from Student's t-distribution; pairwise Mann-Whitney tests with Benjamini-Hochberg FDR control (α=0.05) yield compact-letter displays; Cliff's δ quantifies effect sizes. Results: Hybrid Star-Mesh minimizes latency/loss while maximizing throughput; Ring is consistently inferior; Cluster Tree and ZigBee Star are mid-range; Full Mesh trades redundancy for delay and bandwidth. These models produce actionable guidance for aquaculture (real-time dissolved-oxygen) and urban drinking-water safety, and motivate multi-objective optimization (latency-throughput-energy) toward Pareto-optimal designs.